HP-LT metamorphism in Elba Island: Implications for the geodynamic evolution of the inner Northern Apennines (Italy). (November 2015) - Bianco, Caterina; Brogi, Andrea; Caggianelli, Alfredo; Giorgetti, Giovanna; Liotta, Domenico; Meccheri, Marco
Highlights: Finding of HP-LT metamorphism in Elba Island. Implications for the geodynamic evolution of N. Apennines. Revision of the tectonic units involved in the N. Appennine stacking. Abstract: The inner Northern Apennines belt ( i.e., northern Tyrrhenian Sea and Tuscany) is an Alpine chain affected by high- P metamorphic conditions during its evolution. Although Elba Island is structurally located close to the Adria-Europe suture zone, for several authors it represents a sector of the orogen affected by low- P metamorphism. The involvement of Elba Island tectonic units in high- P metamorphism was only suspected for the sparse presence of phengitic white mica in the metasedimentary rocks. This paper presents the first clear evidence of high- P and low- T metamorphism found in metabasite rocks embedded in the Cretaceous calcschist of eastern Elba Island. Mineral composition of metabasite includes Gln + Cpx + Ep + Ab + Act + Qtz + Ilm ± Ti-oxide ± Spn and is indicative of a former equilibration in the epidote blueschist subfacies and subsequent retrogression in the greenschist facies. Recorded metamorphic conditions are P  = 0.9–1.0 GPa and T  = 330–350 °C. Tectonic discrimination using immobile elements in the metabasite does not point to an oceanic setting. As a consequence, the metasedimentary succession containing metabasite is explained as belonging to the Tuscan continental domain and not to the Ligurian-Piedmont Ocean, as previously interpreted. Our results have two significant implications: (i) it is confirmed and strengthened that the tectonic stacking of the Elba Island units did not occur in a low-pressure context; (ii) Elba Island is now completely reconciled in the tectonic and metamorphic evolution of the inner Northern Apennines.